Hubungan Laba Konservatisma dengan Neraca Konservatisma - Kiryanto Kiryanto; Edy Suprianto (Jurnal Akuntansi dan Bisnis, 2007)
This research hypothesizes and finds that: the first, earnings conservatism, the tendency of firms to recognize bad news in earnings on a more timely basis than good news, is substantially greater in portofolios of firms with lower price-to-book ratios than in portofolios of firms with higher price-to-book ratios. Second, there is the negative association between earnings conservatism and the price-to-book ratios.